Effect of calcination temperature on characteristics of reduced Graphene Oxide (rGO) made from old coconut shell. (February 2019) - Putri, N P; Kusumawati, D H; Agustina, L; Munasir,
Abstract: Coconut shell is one of the carbon sources in nature that can be converted into reduced Graphene Oxide (rGO). There are several methods of rGO synthesis based coconut shell, one of them is hydrothermal method. It's has been synthesized rGO based coconut shell using hydrothermal method with variation of calcination temperature, that is 900˚, 1000˚ and 1100˚C. The samples were characterized by FTIR, XRD and Raman spectroscopy to see the effects of variation of calcination temperature on rGO characteristics. From the FTIR results it was found that the three samples had a C = C group which is the main rGO molecule bond. Besides the 2 main peaks of rGO, XRD results also show the existence of peak impurities, that is sylvite and sulphur peaks. The ratio of ID /IG decreases as the temperature of calcination increases which increases the regularity of the carbon atom and the decreasing defect.